Bioinspired 3D braided artificial ligament with human-like mechanical properties and self-healing capability - Teng, Junnan; Li, Bingqian; Zhao, Xiyang; Wang, Kunyang; Ren, Lei; Xie, Hong; Wang, Xinbo; Su, Yilin; Ren, Luquan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionJoint injuries, a major type of human musculoskeletal disorder, are often accompanied by soft tissue damage, and restoring ligament integrity is a key strategy for reconstructing joint function. However, existing artificial ligaments face a critical challenge: reconciling robust biomechanical performance with intrinsic self-healing capability, especially under cyclic loading and accidental overload conditions. Conventional materials like polyethylene terephthalate (PET) and polytetrafluoroethylene (PTFE) struggle with long-term durability, while emerging self-healing designs are limited by poor mechanical robustness and slow healing kinetics.MethodsThis study developed a self-healing artificial ligament via 3D braiding of shape memory alloy (SMA, Ni50.71Ti49.29) wires and polyethylene (PE) fishing lines, mimicking the hierarchical structure of natural ligaments. The ligament was fabricated with a 1-over-1-under interlock configuration (6 carriers, 180° braid angle) and pre-tensioned (5% strain at 60 °C for 12 h) for structural stabilization. Differential Scanning Calorimetry (DSC), Dynamic Mechanical Analysis (DMA), and mechanical tests (hysteresis, stress relaxation, cyclic loading) were conducted to characterize its thermal and mechanical properties. Electrothermal recovery tests (3–5.5 W power input) evaluated self-healing performance, and a 3D-printed artificial hip joint was used to validate in-situ functionality.ResultsDSC showed the SMA had a thermal hysteresis window of 24.8 °C (Ms=46.5 °C, Mf=27.2 °C, As=58.3 °C, Af=71.3 °C), and DMA revealed an “S”-type storage modulus curve during heating . After 1,000 s of cyclic loading, the self-healing ligament retained ∼73% of initial stress (vs. 37% for conventional ligaments) and had a lower energy dissipation ratio due to SMA’s low damping. Electrothermal tests showed maximum contraction rate increased with pre-strain, and 3–5.5 W power input enabled proportional contraction strain. In artificial hip tests, SMA activation restored ∼95% of initial joint laxity, reducing excessive rotational/translational motion by 26% and 12% respectively.DiscussionThe hybrid SMA-PE design resolves the trade-off between biomechanical performance and self-healing: PE provides foundational tensile strength, while SMA enables electrothermal self-healing via phase transformation. The 3D braided structure replicates natural ligaments’ J-shaped stress-strain behavior, ensuring adaptability to dynamic joint movements. Compared to piezoelectric nanomaterial (PENM)-based designs (focused on proprioception), this ligament prioritizes mechanical stability and rapid self-healing, making it suitable for clinical rehabilitation and assistive devices. Future work will address limitations like wired power supply (via wireless modules) and long-term stability (via anti-degradation coatings).